The EU offer of service trade liberalization in the Doha Round: evidence of a not-yet-perfect customs union - Rolf J. Langhammer (Journal of common market studies, 2005)
While the EU is a customs union in merchandise trade (goods), it has not yet reached this stage of integration in service trade. Trade policies between individual Member States and non-Member States vary in services. Given the remaining national sovereignties in regulating service trade against other EU Member States also, the EU is not yet even a free trade area. How far the EU is from a customs union in service trade is very difficult to assess because of the non-quantitative nature of trade restrictions in this sector. This article gives a first hint of the distance from a customs union by calculating frequency indices of trade measures by refining the 1995 Hoekman index. The database is the EU's first offer in service trade in the WTO Doha round in February 2003. It emerges that the deviation from a customs union is not substantial, but still exists because of differences in national policies against non-Member States which are particularly relevant in the mode of supply via labour flows. Inter alia, policy measures comprise economic needs tests, residence and nationality criteria. The article concludes that there is reason to assume that, in the course of the Doha round negotiations, some if not most of the national measures will be given up. Therefore, multilateral trade negotiations will be instrumental in bringing the EU to a complete customs union as happened in goods trade between 1958 and 1968 when the Dillon and Kennedy rounds helped to complete the customs union in industrial goods.
Keywords: 330; Internationaler Dienstleistungsverkehr; Außenhandelsliberalisierung; EU-Politik; Entwicklungsländer